Brood size of twelve farmland bird species in Sweden during 1962—2001 - Ryttman, Hans; Hall-Karlsson, K Susanna S (Ornis Svecica, 2009)
Several farmland bird species are declining in Sweden. We investigated if the population decreases are linked to smaller broods or a higher rate of unhatched eggs. The number of broods ringed and the average number of nestlings in these broods from 1962 to 2001 were analysed for twelve species: Skylark Alauda arvensis, Swallow Hirundo rustica, House Martin Delichon urbica, Meadow Pipit Anthus pratensis, White Wagtail Motacilla alba, Wheatear Oenanthe oenanthe, Whitethroat Sylvia communis, Starling Sturnus vulgaris, House Sparrow Passer domesticus, Tree Sparrow Passer montanus, Linnet Carduelis cannabina and Yellowhammer Emberiza citrinella. Only two of the investigated species, the Tree Sparrow and the Yellowhammer, showed a statistically significant decline in average brood size over time. We conclude that changes in brood size alone cannot explain the decline in several farmland bird species. The House Sparrow showed an increase in the number of dead nestlings and data for House Sparrow, Tree Sparrow and Whitethroat indicated that a higher rate of unhatched eggs might be a problem.